Is the silver–alkene interaction a useful new supramolecular synthon? - Burgess, Jennifer; Steel, Peter J. (Coordination chemistry reviews, 2011)
The use of the silver–alkene interaction in coordination and supramolecular chemistry is surveyed in this review. Although organometallic complexes of ethene date back almost 200 years to the historic example of Zeise's platinum salt, the use of alkenes as donor ligands for silver(I) has a much more recent history. A diverse range of interesting silver–ethene complexes have been reported in recent years, whilst numerous discrete silver(I) complexes of structurally diverse olefinic ligands have been the subject of much study over the last fifty years. More recently, ligands containing multiple alkene subunits have been used for the synthesis of 0-, 1-, 2- and 3D supramolecular assemblies, which is the major focus of this review.